Bacteriological study of otogenic cerebral abscesses: chemotherapeutic role of metronidazole. Issue 6093 (15th October 1977) - Ingham, H R; Slekon, J B; Roxby, C M
Abstract : In nine consecutive patients with otogenic cerebral abscesses a mixed growth of aerobic and obligate anaerobic bacteria was isolated from the pus in five patients, and in the remaining four obligate anaerobes were the sole isolates. The commonest obligate anaerobe isolated was Bacteroides fragilis, which was present in all but one patient. The patients were all treated with metronidazole for the anaerobic organisms and with appropriate chemotherapy against the aerobic organisms isolated. All the patients recovered and only one was left with a neurological deficit. As otogenic cerebral abscesses constitute a major proportion of all cerebral abscesses, the use of metronidazole against obligate anaerobic bacteria, which tend to dominate in such abscesses, should reduce the high mortality from this condition.